A solar assisted heat pump system for desalination - Mohd. Amin, Zakaria; Hawlader, Mohammad Nurul Alam; Karim, Azharul (IIUM Press, 2011)
This paper includes the performance of a solar assisted heat pump desalination system. Renewable, solar and ambient, energy and waste heat from air conditioning system are used for the production of fresh water. The experiment was conducted under meteorological conditions of Singapore ( 1'21'N; 103'55'E). The coefficient of performance (COP) for the heat pump was around 5.5 for the compressor running at 30 Hz, where the performance ratio (PR) was 1.2. For the pre-heating of feed water to the evaporation chamber, a single glazed collector of 2.O m2 was used. An unglazed solar evaporator-collector was used to collect solar and ambient energy in the heat pump cycle. The efiiciency of the evaporator collector was much higher than the conventional solar collector. The system has an average water production rate of 10 kg/hr.